PENGGUNAAN OMOIYARI DALAM ANIME KAGAMI NO KOJOU - Theresa, Avina; Yuniarsih (Universitas Negeri Jakarta, 2024)
This study aims to determine the function of omoiyari and the factors that influence the use of omoiyari in the anime Kagami no Kojou. This is due to the vulnerable attitude of Japanese people which gives rise to a tendency for Japanese people to communicate indirectly, thus requiring a person to have an omoiyari attitude or high sensitivity to understand the meaning of what the other person is saying. So as a foreign language learner it is important to know the concept of omoiyari which is closely embedded in Japanese society. A total of 22 data were taken from the animated film entitled Kagami no Kojou. This study was analyzed using a qualitative descriptive methods. The data was analyzed using spoken events using Dell Hymes' SPEAKING method. Then analyze and classify the function of omoiyari based on Lebra's theory, and determine the factors underlying the use of omoiyari. The results of the analysis of 22 data, six functions of omoiyari were found, namely 4 data were maintaining of consensus, 9 data were optimization of comfort, 2 data were sentimental vulnerability functions, 3 data were the social echo effect, 2 data were intuitive communication, and 4 data were guilt. Meanwhile, the factors underlying the use of omoiyari are age, gender, situation and groups.